(untitled) (Heritage, 2020)
Primary school in Kosovska Mitrovica under its current name `Branko Radicevic` was founded in 1920. It has had successful development in every aspect of education ever since. The school built of solid material with four classrooms and one staffroom was erected by Kosovska Mitrovica citizen`s donations. After its completion it turned out to be one of most beautiful buildings in this town. After the World war II it was named as `Prva osnovna skola` ( The First Serbian primary school). Due to the number rise of children and the fact the existing facilities were insufficient a new school was built in Lisic Polje .The school was renamed in 1956 as `Branko Radicevic` after the famous poet from the Serbian Romantic period .The school is nearing anniversary of a century long successful work. During that time a numerous number of generations of pupils went to the school.